Parliamentary Immunity Limits Established for the Members of the House of Representatives of Jordan in Jordanian Legislation - Al-Laymoon , Awad Rajab (Dirasat: Shari'a and Law Sciences, 2021)
The current study has examined the scope and limits of the substantive and procedural immunity established for members of the house of representatives of Jordan in accordance with the provisions of the constitution. Legal provisions have stipulated that substantive immunity is limited to expressing opinions and words within the Parliament. Additionally, the procedural immunity was only etablished during the session of the National Assembly, which requires the authorization of the council for the purposes of arrest and trial if a member of the National Assembly commits a criminal offence. The problem of the study stems from confusion and difference in the context of the varying interpretation of crime’s spatial and temporal scope and the conflicts between the statutes of the House of Representatives and the Senate regarding the extension of the scope and coverage of immunity. The study used the descriptive approach based on the analysis of legal texts to achieve the objectives of the study. The study concluded a set of results and recommendations; the most important of which are that the Jordanian legal system and the judiciary within the scope of immunity has expanded in immunity’s temporal scope to include actions committed before being a parliament member. The researcher has recommended that Article (86) should be amended so that immunity applies to all criminal crimes so that it includes Misdemeanors and offenses, instead of being restricted to felonies only.